Musical inventions : DIY instruments to toot, tap, crank, strum, pluck, and switch on - Ceceri, Kathy (Maker Media, 2017)
People have been playing music on homemade instruments for thousands of years. But creating new instruments is much more than an art form. When you want to make a note sound higher or lower, you have to change the sound waves coming out of the instrument. That's science! When you explore the way different materials produce different sounds, that's engineering. When you speed up or slow down a song, you're counting beats -- using math. And technology makes electronic instruments and devices to record and play back music possible.